Correlation Theory of the Maxillary Central Incisor, Face and Dental Arch Shape in the Serbian Population - Milena Kostić; Nadica S. Đorđević; Nikola Gligorijević; Marija Jovanović; Ermin Đerlek; Kosta Todorović; Goran Jovanović; Jelena Todić; Marko Igić (Medicina, 2023)
Background and Objectives: According to the modified Williams theory, the shape of the maxillary central incisor corresponds to the shape of the maxillary alveolar ridge (dental arch) and the shape of the face. Moreover, the standards of beauty suggest that the center of the face of an individual with a full set of teeth should match the center of the maxillary and mandibular dental arches. The purpose of this study is to conduct a comparative cross-sectional study on the matching of the shape of the face, maxillary central incisor and maxillary dental arch as well as the matching of the midfacial line and dental arches in subjects with complete dentition. Materials and Methods: The study included 90 subjects of both sexes. The matching of the shape of the face and midfacial line, i.e., dental arches and maxillary incisors, was determined by analysing photographs, whereas the shape of the dental arch was determined by analysing plaster models. Results: No significant gender-related differences were found either in the shape of the maxillary central incisor that matched the shape of the maxillary dental arch (p = 0.349) or in the shape of the dental arch that matched the shape of the face (p = 0.697). However, a significant difference was noted in the shape of the teeth that matched the shape of the face (p = 0.043), which was more significantly impaired in men. In addition, the matching of the mid-face and the mid-dental arch was significantly greater in women (p = 0.016). Conclusions: The modified Williams theory was confirmed in most subjects, thus it can be considered a relevant guideline when determining the shape of teeth after their loss. The highest percentage of matching in both sexes was with the shape of the face and dental arch. There was no positive correlation between the middle of the maxillary and mandibular dental arch in most cases.